Accessing Cationic α‐Silylated and α‐Germylated Phosphorus Ylides. Issue 1 (9th December 2021) - Krämer, Felix; Radius, Michael; Hinz, Alexander; Dilanas, Melina E. A.; Breher, Frank
Abstract: The synthesis and full characterization of α‐silylated (α‐SiCPs; 1 –7 ) and α‐germylated (α‐GeCPs; 11 –13 ) phosphorus ylides bearing one chloride substituent R3 PC(R 1 )E(Cl)R 2 2 (R=Ph; R 1 =Me, Et, Ph; R 2 =Me, Et, i Pr, Mes; E=Si, Ge) is presented. The molecular structures were determined by X‐ray diffraction studies. The title compounds were applied in halide abstraction studies in order to access cationic species. The reaction of Ph3 PC(Me)Si(Cl)Me2 (1 ) with Na[B(C6 F5 )4 ] furnished the dimeric phosphonium‐like dication [Ph3 PC(Me)SiMe2 ]2 [B(C6 F5 )4 ]2 (8 ). The highly reactive, mesityl‐ or i Pr‐substituted cationic species [Ph3 PC(Me)SiMes2 ][B(C6 F5 )4 ] (9 ) and [Ph3 PC(Et)Si i Pr2 ][B(C6 F5 )4 ] (10 ) could be characterized by NMR spectroscopy. Carrying out the halide abstraction reaction in the sterically demanding ether i Pr2 O afforded the protonated α‐SiCP [Ph3 PCH(Et)Si(Cl) i Pr2 ][B(C6 F5 )4 ] (6 dec ) by sodium‐mediated basic ether decomposition, whereas successfully synthesized [Ph3 PC(Et)Si i Pr2 ][B(C6 F5 )4 ] (10 ) readily cleaves the F−C bond in fluorobenzene. Thus, the ambiphilic character of α‐SiCPs is clearly demonstrated. The less reactive germanium analogue [Ph3 PC(Me)GeMes2 ][B3, 5‐(CF3 )2 C6 H3 4 ] (14 ) was obtained by treating 11 with Na[B3, 5‐(CF3 )2 C6 H3 4 ] and fully characterized including by X‐ray diffraction analysis. Structural parameters indicate a strong CYlide −Ge interaction with high double bond character, and consequently the C−E (E=Si, Ge) bonds in 9, 10 and 14 were analyzed with NBO and AIM methods. Abstract : Competition rules ! α‐Silylated and ‐germylated phosphorus ylides of the general formula R3 PC(R 1 )E(Cl)R 2 2 bearing one chloride substituent on the group 14 element were synthesized and fully characterized. Chloride abstraction reactions provided access to dimeric or monomeric cations featuring a high fluoride ion affinity despite the relatively strong Cylide −E interaction with high double bond character.